22
$\begingroup$

I'm interested in the integral $$ I=\int_{0}^\infty\frac{dx}{\left(1+\frac{x^3}{1^3}\right)\left(1+\frac{x^3}{2^3}\right)\left(1+\frac{x^3}{3^3}\right)\ldots}.\tag{1} $$ So far I have been able to reduce this integral to an integral of an elementary function in the hope that it will be more tractable $$ I=\frac{8\pi}{\sqrt{3}}\int_{-\infty}^\infty\frac{e^{ix\sqrt{3}}\ dx}{\left(e^x+e^{-x}+e^{ix\sqrt{3}}\right)^3},\tag{2} $$ using the approach from this question. In that question it was also proved that $$ \int_{-\infty}^\infty\frac{dx}{\left(e^x+e^{-x}+e^{ix\sqrt{3}}\right)^2}=\frac{1}{3},\tag{3} $$ which gives some indication that the integral in the right hand side of $(2)$ might be calculable.

Also note that the integrand in $(1)$ can be expressed as $$ \Gamma(x+1)\left|\Gamma\left(1+e^{\frac{2\pi i}{3}}x\right)\right|^2. $$

Bending the contour of integration in the integral on the RHS of $(2)$ one obtains an alternative representation $$ I=8\pi\int_0^\infty\frac{e^{x\sqrt{3}}~dx}{\left(2\cos x+e^{x\sqrt{3}}\right)^3}.\tag{4} $$

There are some calculable integrals containing the infinite product $\prod\limits_{k=1}^\infty\left(1+\frac{x^3}{k^3}\right)$, e.g. $$ \int_{0}^\infty\frac{\left(1-e^{\pi\sqrt{3}x}\cos\pi x\right)e^{-\frac{2\pi}{\sqrt{3}}x}\ dx}{x\left(1+\frac{x^3}{1^3}\right)\left(1+\frac{x^3}{2^3}\right)\left(1+\frac{x^3}{3^3}\right)\ldots}=0. $$

Q: Is it possible to calculate $(1)$ in closed form?

$\endgroup$
25
  • $\begingroup$ I'm not sure to what degree this may be helpful, but have you tried anything along the lines of contour integration? $\endgroup$ Nov 27, 2016 at 13:08
  • 2
    $\begingroup$ @Dr. Wolfgang Hintze but $\sin$ has $n^2$ in its infinte product formula, not $n^3$ $\endgroup$
    – tired
    Nov 27, 2016 at 20:12
  • 1
    $\begingroup$ @Nemo to be honest i think your questions might be better suited for MathOverflow... $\endgroup$
    – tired
    Nov 27, 2016 at 20:28
  • 1
    $\begingroup$ The numerical value of the integral is 0.9726754529705... $\endgroup$ Nov 27, 2016 at 20:51
  • 1
    $\begingroup$ @Nemo In (2) : shouldn't it read 8 pi instead of 4 pi ? $\endgroup$ Nov 28, 2016 at 13:41

1 Answer 1

3
$\begingroup$

define:

$$ Q^n(x) = \prod_{a=1}^n{1-\left(\frac{x}{a}\right)^3} = \left(1-\left(\frac{x}{a}\right)^3\right) \cdot\prod_{b\ne a}{1-\left(\frac{x}{b}\right)^3} = \left(1-\left(\frac{x}{a}\right)^3\right)\cdot Q_a(x) $$

using:

$$\begin{align*} (a) && & 1-\left(\frac{x}{a}\right)^3 = 0 \Leftrightarrow x=az_i, \; (z_i)^3=0.\; i=0,1,2 \\ (b) && & \frac{d}{dx}\left(1-\left(\frac{x}{a}\right)^3\right) = -3\frac{x^2}{a^2}; \; (x=az_i)\; -3\frac{\bar{z}_i}{a} \\ (c) && & (b\ne a) \Rightarrow1-\left(\frac{az_i}{b}\right)^3 = 1-\left(\frac{a}{b}\right)^3 \\ (d) && & \frac{d}{dx}Q^n(x)=\left(1-\left(\frac{x}{a}\right)^3\right)Q'_a(x) - 3\frac{x^2}{a^3}Q_a(x) \\ (a,b,c,d) \Rightarrow (e) && & Q'(az_i)=0-3\frac{\bar{z}_i}{a}Q_a(az_i) = -3\frac{\bar{z}_i}{a} \prod_{b\ne a}{\left(1-\left(\frac{a}{b}\right)^3\right)} = -3\frac{\bar{z}_i}{a}P(a) \end{align*}$$


$$\begin{align*} \frac1{Q^n(x)} && & \stackrel{pfd}{=} \sum_{a=1}^n{\sum_{i=0}^3{\frac1{(x-az_i)\cdot Q'_a(x)}}} \\ && & \stackrel{(e)}{=} \sum_{a=1}^n{\sum_{i=0}^3{\frac1{-3\bar{z_i}(x-az_i)} \cdot \frac{a}{P(a)}}} \\ && & = \sum_{a=1}^n{\frac{a}{P(a)}\sum_{i=0}^3{\frac{z_i}{-3(x-az_i)}}}\\ && & = \sum_{a=1}^n{\frac{a}{P(a)}\cdot\frac{a^2}{a^3-x^3}}\\ \end{align*}$$


$$\begin{align*} \int_0^{\infty}{\frac1{Q_n(-x)}dx} && & = \int_0^{\infty}{ \sum_{a=1}^n{\frac{a}{P(a)}\cdot\frac{a^2}{a^3+x^3}}dx} \\ && & = \sum_{a=1}^n{\frac{a}{P(a)}\cdot\int_0^{\infty}{\frac{a^2}{a^3+x^3}dx}}\\ && & = \sum_{a=1}^n{\frac{a}{P(a)}\cdot\frac{2\pi}{3\sqrt{3}}} \\ \end{align*}$$


$$\begin{align*} \lim_{n\to\infty}\int_0^{\infty}{\frac1{Q_n(-x)}dx} && & = \lim_{n\to\infty}\sum_{a=1}^n{\frac{a}{P(a)}\cdot\frac{2\pi}{3\sqrt{3}}}\\ && & = \frac{2\pi}{3\sqrt{3}}\lim_{n\to\infty}\sum_{a=1}^n{\frac{a}{P(a)}}\\ \end{align*}$$


Answer:

$$\frac{2\pi}{3\sqrt{3}}\sum_{a=1}^{\infty}{a\prod_{b\ne a}{\left(1-\left(\frac{a}{b}\right)^3\right)^{-1}}}$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.